2008
DOI: 10.1080/01459740701831401
|View full text |Cite
|
Sign up to set email alerts
|

Smoking among Doctors: Governmentality, Embodiment, and the Diversion of Blame in Contemporary China

Abstract: How and to what effect have physicians in China become frequent cigarette smokers and blamed as engines of nationwide tobacco-induced suffering? Building on governmentality heuristics, I argue that multilevel interactions of biopolitics and male embodiment have been especially significant in shaping these phenomena. Of the effects gleaned in my fieldwork ongoing since 2003, the most important is a deflection of responsibility for tobacco-induced death away from incoherent leadership decisions--some aimed at pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Groups particularly subject to the gifting norm include businessmen, government officials and doctors who find songyan , fayan and smoking to be a critical part of professional and personal success 2 87 88. The practice has contributed to an estimated 60% smoking prevalence in 1996 among male Chinese doctors 88 89.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groups particularly subject to the gifting norm include businessmen, government officials and doctors who find songyan , fayan and smoking to be a critical part of professional and personal success 2 87 88. The practice has contributed to an estimated 60% smoking prevalence in 1996 among male Chinese doctors 88 89.…”
Section: Discussionmentioning
confidence: 99%
“…The practice has contributed to an estimated 60% smoking prevalence in 1996 among male Chinese doctors 88 89. Because China's doctors bear some responsibility for the country's high smoking rates, doctors should cease offering and accepting cigarettes among themselves and from patients' families.…”
Section: Discussionmentioning
confidence: 99%
“…A major barrier to the implementation of smoke-free policies in Chinese hospitals is the common practice of patients’ relatives proffering cigarettes to doctors 30. It has also been reported that smoking behavior by the director and other senior members of the ward hospital staff influences smoking behavior by junior surgeons 35.…”
Section: Discussionmentioning
confidence: 99%
“…Augmenting these streams have been ethnographic descriptions of cigarette smoking framed vis-à-vis views of wellness (Mock 2000), social exchange (Kohrman 2008), and substances such as marijuana (Lipset 2006) and betel-nut (Reid 1985, Strickland 2002 (Stellman & Resnicow 1997) to genetics (Swan et al 2003) and the use of alcohol (Cameron & Jones 1985). Nearly all these studies approach cigarette smoking as acutely addictive; some consider how biological habituation is shaped by employment (Longo et al 2001), norms (Hosking et al 2009), and diverse cross-cultural expressions of dependency (Quintero & Nichter 1996, Shadel et al 2000.…”
Section: Usage Addiction and Cessationmentioning
confidence: 99%
“…Bringing anthropological methods to bear on how within or across states some governments interdict while others promote cigarettes can offer productive fodder for current theoretical work on the ways mass promotion of life and death by the state are mutually dependent and frequently mobilized today under the rubrics of international development, public health, and consumer fulfillment (Agamben 1998;Banerjee 2006;Fassin 2007;Kohrman 2007Kohrman , 2008.…”
Section: Global Public Health Government and State Formationmentioning
confidence: 99%